Charité Caesarean Birth Improves Birth Experience in Planned and Unplanned Caesarean Sections While Maintaining Maternal and Neonatal Safety: A Prospective Cohort Study - Laura Radtke; Ricarda Dukatz; Carolin Biele; Alexander Paping; Khaled Sameez; Christine Klapp; Wolfgang Henrich; Anna M Dückelmann (IMR Press, 2022)
Background: In this study, we aimed to assess the safety of a modified caesarean delivery (Charité caesarean birth) in an extended frame of indications, and to examine its impact on parents' birth experience and long-term effects. Methods: This prospective cohort study was performed from January to June 2019. A standardized questionnaire was given to all women who gave birth as an inpatient delivery. Eight months after hospital discharge, all women who gave consent were sent a follow-up questionnaire including questions on current feelings, breast feeding, bonding, and support system, as well as a screening for postnatal depression. Indications for caesarean delivery included preterm birth, fetal malpresentation, fetal malformation, twin pregnancy, and maternal pre-existing conditions. Results: The study cohort included 110 women. The mode of delivery was spontaneous in 49%, per vacuum extraction in 15%, conventional caesarean section in 7%, and Charité caesarean birth in 29%. The groups with Charité versus conventional caesarean delivery did not significantly differ in neonatal admission rates, umbilical cord parameters, maternal blood loss, or duration of surgery. Compared to conventional caesarean delivery, women who underwent a Charité caesarean delivery were significantly more satisfied with their birth experience. At follow-up, the mode of delivery was not associated with significant differences in postnatal depression, breast feeding, or bonding parameters. Conclusions: Outside of emergency situations, Charité caesarean birth improves patients' well-being, without increased maternal and neonatal morbidity.